Resilient Teacher: Harnessing The Adversity Quotient to Navigate School Crises - Tolero, Josue A.; Acasio, Girlie G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study investigates the relationship between teachers’ adversity quotient (AQ) and their crisis management practices in public schools in the District of Cabangan using a descriptive research design involving 208 teacher-respondents. The AQ of teachers was assessed across four dimensions Control, Ownership, Reach, and Endurance while crisis management practices were examined in terms of prediction, prevention, preparedness, performance, and post-crisis action. Data were analyzed using percentage, weighted mean, and Pearson correlation. Findings revealed that teachers demonstrated an “Above Average” level of AQ, indicating resilience and adaptability in managing adversities, although ownership and accountability remained areas for improvement. Teachers also exhibited positive crisis management practices, particularly in prediction, prevention, and performance, while long-term crisis planning and communication were identified as aspects needing enhancement. The results further showed a negligible correlation between teachers’ AQ and their crisis management practices, suggesting that these variables operate independently of one another. Demographic factors such as age, length of service, and educational attainment showed minimal influence on both AQ and crisis management practices, except among younger teachers who displayed distinct attitudes toward crisis prevention. Based on the findings, the study proposed an action plan aimed at strengthening teachers’ AQ and crisis management capabilities through resilience training, continuous professional development, and improved communication systems to enhance preparedness and sustain a safe and productive learning environment during future crises.